Selected physico-chemical properties of extrudates from white yam (Dioscorea rotundata) and bambara nut (vigna subterranean) blends (2013)
"This study was conducted to investigate effects of extrusion conditions on physicchemical properties of blend of yam and bambara nut flours. Blend of white yam grit (750 µm) and Bambara nut flour (500 µm) in ratio 4:1 respectively was extrusion cooked at varying screw speeds 50-70rpm, feed moisture 12.5-17.5% (dry basis) and barrel temperatures 130-150 E5oC. Extrusion variables employed included barrel temperature (BT), screw speed (SS) and feed moisture content (FM), while physico-chemical properties of extrudates investigated were expansion ratio (ER), bulk density (BD) and trypsin inhibition activity (TIA). The results revealed that all the extrusion variables had significant effects (p<0.05) on the product properties considered in this study. Expansion ratio values ranged 1.55-2.06; bulk density values ranged 0.76-0.94 g/cm3, while trypsin inhibition activities were 1.01-8.08 mg/l00g sample."